Ayat Al-Quran Tentang Alam Takambang Jadi Guru dalam Lukisan Kaligrafi - Rizki Hamdani (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
Indonesia is known for its rich ethnic and cultural diversity, one of which is the Minangkabau ethnic group, renowned for its strong ancestral traditions. This research aims to visualize the philosophy of "Alam Takambang Jadi Guru" upheld by the Minangkabau community through Islamic calligraphy painting. The method used is a descriptive approach with the exploration of calligraphy art elements inspired by the works of national calligraphy artists such as H. Purwanto Zain. The findings of the study show that this philosophy serves not only as a life guide but also as an inspiration in calligraphy art that combines traditional and religious values. The implications of this work are a form of spiritual devotion and an effort to preserve the Minangkabau culture, rich in noble values. In conclusion, the resulting calligraphy art is able to inspire the next generation to continue appreciating nature as a teacher and to understand the greatness of Allah SWT in every aspect of life.